2007
DOI: 10.22260/isarc2007/0045
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a General-Purpose Autonomous Robot

Abstract: This paper presents the ongoing research into the design and development of a general-purpose autonomous robot. The major components of the robot are four ultrasonic sensors, one electronic compass, three microprocessors, a laptop computer, and three motors for three wheels. Software architecture was developed to process the information obtained from the sensors, plan the motion of the robot, and send the commands to the motors. This allows the robot to operate independently of human control thus fulfilling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…This result is in line with the findings of Ma et al (2017) and Osterrieder et al (2020), who concluded that human and non-human actors' interaction greatly supported human resources and their decision-making capabilities. It is interesting to note that our research confirmed that implementing autonomous robots does not support human resources in SMEs, which is consistent with the determination of Gu et al (2007), as an autonomous robot can perform tasks without human resources, in other way, these robots rather replace human resources.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This result is in line with the findings of Ma et al (2017) and Osterrieder et al (2020), who concluded that human and non-human actors' interaction greatly supported human resources and their decision-making capabilities. It is interesting to note that our research confirmed that implementing autonomous robots does not support human resources in SMEs, which is consistent with the determination of Gu et al (2007), as an autonomous robot can perform tasks without human resources, in other way, these robots rather replace human resources.…”
Section: Discussionsupporting
confidence: 85%
“…• Autonomous robots: an autonomous robot is an intelligent machine capable of performing tasks without explicit human involvement (Gu et al, 2007). • Cobot: collaborative robots are intended to work and physically interact alongside human workers in a shared workspace (Cohen et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%